Evaluation index of wind resistance performance of dust suppressant and its application - HAN Fangwei; XU Manping; LI Wei; ZHU Linling; MA Liang; WANG Jia; FAN Simeng (矿业科学学报)
This study proposes three evaluation indexes for evaluating the wind resistance of mine dust inhibitors, namely average loss rate per unit mass (ALRPUM) of dust suppressant, average suppression rate per unit mass (ASRPUM) of dust suppressant, and critical effective mass (CEM). The wind tunnel simulation experiment was carried out on coal samples by controlling wind speed, blowing time, blowing angle, and spraying quality of dust suppressant. Results show that the increase in wind speed leads to an increase in the ALRPUM of dust suppressant and pure water, and a significant decrease in the ASRPUM. The increase in blowing erosion time also leads to an increase in the ALRPUM of dust suppressant and pure water, while the ASRPUM of dust suppressant shows a slow downward trend. With the increase of blowing angle, the ALRPUM of dust suppressant exhibits a trend of initially decreasing and then increasing, reaching its minimum at an angle of 60°. The ASRPUM of dust suppressant shows an initial increase and subsequent decrease. The dust suppressant reaches its maximum effect when the spraying quality of the dust suppressant reaches the CEM.